2010
DOI: 10.1007/s00296-010-1392-7
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of TNF-α promoter –308A/G polymorphism and SLE susceptibility in Asian populations

Abstract: The aim of this study was to summarize results on the association of tumor necrosis factor-α (TNF-α) promoter -308A/G polymorphism with systemic lupus erythematosus (SLE) susceptibility in Asian populations by using the meta-analysis. We searched all the publications about the association between TNF-α promoter -308A/G polymorphism and SLE in Asian populations from PubMed, Elsevier Science Direct, Chinese Biomedical Literature Database (CBM), Chinese National Knowledge Infrastructure (CNKI), and Wanfang (Chine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Moreover, the role of Th1 response against L. major infection was also demonstrated in animal model of L. major [9,10]. Out of all studied Th1 cytokines, TNFα and IFN-γ were found to be critical for the initiation of preventive immunity against all studied L. species, particularly L. major [10][11][12][13]. TNF-α-308G/A polymorphism was well studied in several autoimmune/inflammatory diseases, the A allele of TNFα (308G/A) was reported to have higher transcriptional activity by 6-7 folds as compared with the common G allele [14,15].…”
Section: Introductionmentioning
confidence: 87%
“…Moreover, the role of Th1 response against L. major infection was also demonstrated in animal model of L. major [9,10]. Out of all studied Th1 cytokines, TNFα and IFN-γ were found to be critical for the initiation of preventive immunity against all studied L. species, particularly L. major [10][11][12][13]. TNF-α-308G/A polymorphism was well studied in several autoimmune/inflammatory diseases, the A allele of TNFα (308G/A) was reported to have higher transcriptional activity by 6-7 folds as compared with the common G allele [14,15].…”
Section: Introductionmentioning
confidence: 87%
“…A significant genetic association between TNF-α promoter −308A/G polymorphism and SLE susceptibility in Asian populations, and in European-derived populations was detected in Zou et al (2011) and Lee et al (2006) meta-analysis respectively.…”
Section: Association Between Tnf-α Genetic Polymorphisms and Autoimmumentioning
confidence: 95%
“…TNF is a cytokine secreted by macrophages and an immunomodulatory molecule that can alter the balance of T-regulatory cells and participate in the pathogenesis of SLE [43]. Several studies have shown that TNF-α gene polymorphisms are closely related to the susceptibility to SLE [44][45][46]. IL6 is a cytokine with multiple biological functions in immunity and tissue regeneration, which is associated with the pathogenesis of SLE [47].…”
Section: Discussionmentioning
confidence: 99%